ChemInform Abstract: An Efficient Four‐Component Approach for the Synthesis of Novel 5‐Methyl‐4‐(2‐ (3‐methyl‐4‐nitroisoxazol‐5‐yl)‐1‐arylethyl)‐1H‐pyrazol‐3‐ol Derivatives and Their Antibacterial Study. Issue 52 (6th December 2016) - Muthineni, Narmada; Satish Kumar, Nandigama; Chandrasekhara Rao, L.; Dileep Kumar, V.; Misra, Sunil; Raju Chowhan, L.; Meshram, H. M.
Abstract: Title compounds have been prepared via 4‐component reaction of hydrazine hydrate, ethyl aceto/benzoyl‐acetate ((I) or (VII)), 3, 5‐dimethyl‐4‐nitro‐isoxazole (II) and (het)arylaldehydes ((III) and (V)) including 1‐phenyl‐3‐arylpyrazol‐4‐carbaldehydes (IX).